2022
DOI: 10.3390/bs12090326
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment in the Workplace: Consequences and Perceived Self-Efficacy in Women and Men Witnesses and Non-Witnesses

Abstract: Despite the numerous advances made in Italy over the years in the study of sexual harassment in the workplace (SHW), research has focused exclusively on victims, perpetrators, and their relationships, and not on the consequences that the experience of sexual harassment can produce in witnesses. The present study aims to address this gap by examining how the indirect experience of SHW, in conjunction with variables such as gender, age, self-efficacy, and coping strategies, affects the mental health status of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
0
8
0
1
Order By: Relevance
“…Due to their weakness and lack of strength compared to men, women are frequently the victims of sexual harassment. The findings indicate the need for workplace sexual harassment intervention (Maran et al, 2022). Both men and women who witness sexual harassment experience psychological consequences, tiredness, depression, and unpleasant sensations as a result of their experience.…”
Section: Workplace Harassmentmentioning
confidence: 87%
“…Due to their weakness and lack of strength compared to men, women are frequently the victims of sexual harassment. The findings indicate the need for workplace sexual harassment intervention (Maran et al, 2022). Both men and women who witness sexual harassment experience psychological consequences, tiredness, depression, and unpleasant sensations as a result of their experience.…”
Section: Workplace Harassmentmentioning
confidence: 87%
“…The upcoming research can also concentrate on both gender (men and women) as this study was limited to female. Hence, it is recommended that future studies be conducted for both genders, as the current trend also showed men are in the rising victims of sexual harassment (Acquadro et al, 2022). Another recommendation is to expand the scope of the study to include the four major states with the highest number of online sexual harassment cases.…”
Section: Discussionmentioning
confidence: 99%
“…The costs of WSH likely come not only from the harassed women but also from their co-workers who witness WSH. In this regard [ [24] , [25] , [26] ], have found that colleagues who witness WSH are likelier to suffer emotional and psychological consequences than their non-witness counterparts. These consequences can affect productivity, and they can also trigger counterproductive behaviors.…”
Section: Proposed Modelmentioning
confidence: 99%